The uses of Wikidata for galleries, libraries, archives and museums and its place in the digital humanities. Issue 2 (March 2019) - Cook, Stacey
Abstract : As open source, collaborative and crowd-sourced media become increasingly popular, it is essential that the community of galleries, libraries, archives and museums (GLAMs) take a central role within these digitally based projects. This article looks specifically at Wikimedia's Wikidata project and provides an overview of Wikidata's various uses for GLAMs. It gives a brief outline of where Wikidata fits into broader digital humanities scholarship and how it can contribute to digital humanities projects, whether within academia, or through public engagement. Finally, it provides examples of some potential digital humanities projects that GLAMs can explore to foster further engagement with digital scholarship and the larger Wikimedia community, as well as finding increasingly creative, informative, innovative and meaningful ways to disseminate and present the reliable data and source information which they hold.